XLIMus drug eluting stent: A randomIzed controlled Trial to assess endothelialization. The XLIMIT trial. (June 2019) - Testa, Luca; Pero, Gaetano; Bollati, Mario; Casenghi, Matteo; Popolo Rubbio, Antonio; Cuman, Magdalena; Moreno, Raul; Serra, Antoni; Gomez, Joan Antoni; Bedogni, Francesco
Abstract: Background: Thin strut 3rd generation drug eluting stents offer the potential advantage over the previous generation of better technical performance and reduced neointimal proliferation parameters, which are linked to mid and late term device failure. Aim: To evaluate the performance of the Xlimus sirolimus-eluting stent (SES) against the Synergy everolimus-eluting stent (EES) in terms of device reendothelialization in patients undergoing PCI for coronary artery disease (CAD). Methods: XLIMIT is a multicenter randomized controlled trial targeting 180 patients requiring percutaneous coronary interventions (PCI). Patients will be treated with Xlimus SES or Synergy EES implantation and randomization will be performed in a 2:1 ratio. The primary endpoint will be the reendothelialization grade of the Xlimus stent in terms of strut coverage and neointimal hyperplasia volume as compared to Synergy. Secondary endpoints will be represented by clinical and procedural outcomes. The first patient was enrolled on February 2019. Conclusions: A clearer understanding of the endothelialization process of new generation DES could significantly impact the treatment with dual antiplatelet therapy in the future. Moreover, although not powered for clinical end-points, the XLIMIT trial will provide randomized data in a population with minimal exclusion criteria. Trial registration: ClinicalTrials.gov Identifier:NCT03745053 . Registered on November 19, 2018.